1998
DOI: 10.1111/j.1532-5415.1998.tb03806.x
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Year Follow‐Up of Geriatric Consults in the Emergency Department

Abstract: The older patients seen in the ED of the acute care hospital for whom multidisciplinary geriatric consult is requested constitute a high-risk population. Within 2 years after initial consultation, many are dead and more than half have been institutionalized. The results of our follow-up imply the need for multidisciplinary intervention early on in the course of an older patient's ED visit as well as close follow-up after hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
1
28
0
6
Order By: Relevance
“…It was observed that has the age increased, there was also an increase in the ratios of requesting consultations (17). In the study made by Sinoff et al, it was found that of all the consultations requested in the ED, 49.3% were requested for patients in the geriatric age group (18). The results found in this study were generally found to be in conformity with the other studies.…”
Section: Discussionsupporting
confidence: 81%
“…It was observed that has the age increased, there was also an increase in the ratios of requesting consultations (17). In the study made by Sinoff et al, it was found that of all the consultations requested in the ED, 49.3% were requested for patients in the geriatric age group (18). The results found in this study were generally found to be in conformity with the other studies.…”
Section: Discussionsupporting
confidence: 81%
“…37 When possible, previously validated survey instruments are preferable, 38 but for our objectives, no such instrument exists. Therefore, our survey instrument was developed by a detailed review of existing research focused on ED interventions to improve geriatric adult emergency care, 5,6,13,15,20,25,26,32,34,35,[39][40][41][42][43][44][45][46] as well as discussions with a multidisciplinary collaboration of representatives from SAEM, ACEP, the American Geriatrics Society, and the Emergency Nurses Association. This collaboration continues to develop geriatric ED infrastructure, personnel, protocol, and educational guidelines.…”
Section: Survey Content and Administrationmentioning
confidence: 99%
“…Comprehensive geriatrics assessments (CGAs) in the ED have previously been described at other sites. [5][6][7] …”
mentioning
confidence: 99%